1999
DOI: 10.1006/mpev.1998.0598
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Phylogeny in the Drosophila obscura Species Group Based on Combined Analysis of Nucleotide Sequences

Abstract: The Drosophila obscura species group has served as an important model system in many evolutionary and population genetic studies. Despite the amount of study this group has received, some phylogenetic relationships remain unclear. While individual analysis of different nuclear, mitochondrial, allozyme, restriction fragment, and morphological data partitions are able to discern relationships among closely related species, they are unable to resolve relationships among the five obscura species subgroups. A combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 48 publications
5
34
0
Order By: Relevance
“…5 and 6). Many relationships in this group are congruent with other phylogenetic analyses of the obscura species group (Beckenbach et al, 1993;Barrio et al, 1994;Barrio and Ayala, 1997;O'Grady, 1999;Katoh et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…5 and 6). Many relationships in this group are congruent with other phylogenetic analyses of the obscura species group (Beckenbach et al, 1993;Barrio et al, 1994;Barrio and Ayala, 1997;O'Grady, 1999;Katoh et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…The target loci were amplified from each taxon using standard PCR cycling conditions. Oligonucleotides used to amplify the Adh and COII genes are described elsewhere (O'Grady et al, 1998;O'Grady, 1999). PCR products from the Adh gene were then cloned into the TA cloning vector (Invitrogen).…”
Section: Dna Sources Isolation and Sequencingmentioning
confidence: 99%
“…However, it has been shown that in certain cases, nuclear markers can be used to corroborate or refute phylogenetic relationships derived through mtDNA analyses (Baker et al 2001;Macnish et al 2002;Shaw 2002;Slowinski & Lawson 2002). Several studies have shown that multiple locus datasets can produce a biologically reasonable phylogeny from a simultaneous analysis, whereas contradictory phylogenies result from analysis of individual markers (Baker & DeSalle 1997;Gatesy et al 1999a,b;O'Grady 1999). At the very least, inclusion of numerous nuclear loci can provide a stronger analysis of genetic structure and can increase the likelihood of deriving the true species tree by incorporating biparentally inherited markers and sampling across independent evolutionary loci (Baker & DeSalle 1997;Gatesy, et al 1999b;Palumbi et al 2001;Russello & Amato 2003).…”
Section: Discussion (A) Utility Of Nuclear Locimentioning
confidence: 99%
“…Lines depict estimated average trajectories for each phase of speciation and are depicted as linear for simplicity of comparison. species pairs from the Drosophila dataset (Nurminsky et al 1996;DeSalle and Brower 1997;Hilton and Hey 1997;Lemeunier et al 1997;Gleason et al 1998;O'Grady 1999;Harr et al 2000;Rodriguez-Trelles et al 2000;Schawaroch 2002; see Appendix D online). Results of analyses of this smaller dataset (n ϭ 17) were compared with those of the full dataset.…”
Section: Methodsmentioning
confidence: 99%